2015
DOI: 10.1177/1534735415610427
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Interaction of Antioxidant Supplements as Adjuvant Therapy in Cancer Treatment

Abstract: Oxidative stress is a key component in carcinogenesis. Although radiation produces reactive oxygen species, some anticancer agents such as alkylating agents, platinum and antitumor antibiotics exert cytotoxicity by generating free radicals. Nonenzymatic exogenous antioxidants such as vitamins, minerals, and polyphenols can quench ROS activity. However, whether antioxidants alter antitumor effects during radiotherapy and some types of chemotherapy remains unclear. In the present study, we reviewed antioxidants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 116 publications
0
125
0
4
Order By: Relevance
“…Obecně se podávání antioxidantů při léčbě onkologického onemocnění nedoporučuje, a to kvůli možnému snížení účinků léčby, která je často založená na tvorbě volných radikálů [54]. Ve výše uvedené studii na myších zabývající se poškozením plic radiací se porovnával také vliv samotné radiace a radiace v kombinaci se silymarinem na nádor plic, jehož vznik in vivo byl podmíněn chemicky.…”
Section: Závěrunclassified
“…Obecně se podávání antioxidantů při léčbě onkologického onemocnění nedoporučuje, a to kvůli možnému snížení účinků léčby, která je často založená na tvorbě volných radikálů [54]. Ve výše uvedené studii na myších zabývající se poškozením plic radiací se porovnával také vliv samotné radiace a radiace v kombinaci se silymarinem na nádor plic, jehož vznik in vivo byl podmíněn chemicky.…”
Section: Závěrunclassified
“…A systematic review found no benefit of supplemental ascorbate (vitamin C) for overall or progression-free survival in cancer patients, most of whom had breast or colorectal cancer (Jacobs et al 2015). Another systematic review examined treatment efficacy and patient survival with the use of any adjuvant antioxidants during chemotherapy or radiotherapy (Yasueda et al 2016). The trials showed contradictory results, but …”
Section: Clinical Trials Of Antioxidants In Cancer Treatmentmentioning
confidence: 99%
“…Antioxidants are also thought to be beneficial in alleviating the adverse effects of chemotherapy and/or radiotherapy [7]. However, the precise mechanism(s) of action of antioxidants in cancer is not yet fully known and clinical trials have still been reporting inconsistent outcomes [1,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%